2015
DOI: 10.1080/14461242.2014.999400
|View full text |Cite
|
Sign up to set email alerts
|

Informal caring networks for people at end of life: building social capital in Australian communities

Abstract: The care of a person living at home near the end of their life is predominantly provided by family carers with the support of health services such as palliative care. In addition, informal caring networks also contribute at times to the support provided to the dying person and their carer. In this way, these networks can promote social capital in the communities from which they are drawn. This social approach to end of life care enhances community capacity to provide support to those dying at home and their ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 40 publications
0
36
0
1
Order By: Relevance
“…Most health care services involve primary carers at best, highlighting the need for greater efforts to engage with and harness care networks . Developing skills among extended care networks may be especially important to support people in the final stages of terminal cancer, when exhaustion among primary carers is a common reason for admission to hospital . Upskilling extended care networks has potential not only to enable one‐off support but also to develop community capacity to repeat this role for other people in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most health care services involve primary carers at best, highlighting the need for greater efforts to engage with and harness care networks . Developing skills among extended care networks may be especially important to support people in the final stages of terminal cancer, when exhaustion among primary carers is a common reason for admission to hospital . Upskilling extended care networks has potential not only to enable one‐off support but also to develop community capacity to repeat this role for other people in the future.…”
Section: Discussionmentioning
confidence: 99%
“…What little research is available on extended care networks suggests emotional support may be among their key contributions, with increasing significance towards the end of life. 26 While only 19% of carers reported providing emotional support as their sole contribution, we did not ask about the relative time spent on each type of care, so it may be that a much larger proportion provided emotional support predominantly.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has indicated that rural communities have strong informal networks and connections that facilitate well‐being (Rosenberg et al . ). However, this is not unproblematic, and rural communities can also suffer from lack of privacy and an expectation of ‘stoicism’ (Davis et al .…”
Section: Introductionmentioning
confidence: 97%
“…Given much of the psychosocial supportive care in rural communities is informal; we considered this was a gap in the current literature and an important area for research. Previous research has indicated that rural communities have strong informal networks and connections that facilitate well-being (Rosenberg et al 2014). However, this is not unproblematic, and rural communities can also suffer from lack of privacy and an expectation of 'stoicism' (Davis et al 2003;Butow et al 2012;Gunn et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Dying has become firmly located within health care systems, with the result that, for most people, the process of dying is medicalised, individualised, and institutionalised (Howarth, ). However, Kellehear () proposed Health Promoting Palliative Care (HPPC), which has a focus on social change (Rosenberg, Horsfall, Leonard, & Noonan, ), through developing strategies which provide education and social support, encourage interpersonal reorientation and the reorientation of palliative care services, and combat death‐denying health policies and attitudes ().…”
mentioning
confidence: 99%